(untitled) (Current Horticulture, 2024)
Tomato (Solanum lycopersicum L.) is most important vegetable crop for human health. The postharvest handling and management of tomato is prime concern in India because the annual postharvest losses for tomato can reach up to 25 - 40 %. Non-destructive approaches for quantification and monitoring of nutritional and quality aspects of horticultural commodities have come up in a big way in the recent past that can also serves towards better postharvest management. Out of various non-destructive approaches, optical method based on visible-near infrared (Vis-NIR) spectroscopy (hyperspectral imaging and reflectance) is the most important analytical tool that provides spatial and spectral information simultaneously for a commodity towards non destructive assessment of food quality-related parameters. Therefore, an overview with latest developments and applications of hyperspectral imaging and reflectance techniques for the assessment of nutritional and quality parameters of tomato fruits has been discussed. The advantages and disadvantages of this tool along with the future perspectives are also highlighted.